2014
DOI: 10.1161/strokeaha.114.005147
|View full text |Cite
|
Sign up to set email alerts
|

Varying Correlation Between 18 F-Fluorodeoxyglucose Positron Emission Tomography and Dynamic Contrast-Enhanced MRI in Carotid Atherosclerosis

Abstract: Background and Purpose— 18 F-fluorodeoxyglucose positron emission tomography and dynamic contrast-enhanced MRI have been proposed to quantitatively assess plaque inflammation by probing macrophages and neovessels, respectively. We examined their correlation to study the in vivo relationship between macrophage and neovessel activities in atherogenesis. Methods— Forty-one patients (34 men; aged 65±1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 13 publications
1
17
0
2
Order By: Relevance
“…These results are in line with previous studies [20, 23, 2830], where a weak to modest correlation between plaque inflammation and microvasculature was reported. The present study supports the concept that there is a complex interplay between macrophages and plaque microvasculature [28].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in line with previous studies [20, 23, 2830], where a weak to modest correlation between plaque inflammation and microvasculature was reported. The present study supports the concept that there is a complex interplay between macrophages and plaque microvasculature [28].…”
Section: Discussionsupporting
confidence: 93%
“…Magnetic Resonance Imaging (MRI) has emerged as a promising technique to visualize both plaque size and features of plaque vulnerability in vivo [19]. Dynamic contrast-enhanced MRI (DCE-MRI) has developed into a tool for assessment of the atherosclerotic plaque microvasculature [2030], which is thought to be a hallmark of plaque vulnerability [31]. It has been shown that both semi-quantitative [20] and quantitative [2527] DCE-MRI parameters correlate with the amount of microvessels in the plaque.…”
Section: Introductionmentioning
confidence: 99%
“…[300]. W jednym z badań porównywano użyteczność prognostyczną współcześnie stosowanych skal ryzyka pod względem chorobowości i śmiertelności po leczeniu operacyjnym z powodu IZW u 146 osób [301]. W tym badaniu wykazano, że choć skala EuroSCORE II pozwoliła na rozróżnienie śmiertel-ności i chorobowości pooperacyjnej (zwłaszcza występowania udaru), to skala Towarzystwa Chirurgów Klatki Piersiowej dla zapalenia wsierdzia oraz skala De Feo i wsp.…”
Section: Leczenie Operacyjneunclassified
“…Los sistemas de puntuación de riesgo específicos para la cirugía de la EI se han desarrollado: a) a partir de la base de datos de la Society of Thoracic Surgeons usando datos de 13.617 pacientes 299 , y b) un sistema específico de puntuación de riesgo de EVN desarrollado a partir de un único centro con datos de 440 pacientes de De Feo et al 300 . Un estudio ha comparado la utilidad pronóstica de estos sistemas contemporáneos de puntuación del riesgo de mortalidad y morbilidad después de la cirugía de EI en 146 pacientes 301 . Los resultados indican que aunque el EuroSCORE II discrimina mortalidad y morbilidad posoperatoria (en especial, accidentes cerebrovasculares), el sistema de clasificación de riesgo en la endocarditis de la Society of Thoracic Surgeons y de De Feo et al 300 es superior a la hora de predecir la mortalidad posoperatoria después de la cirugía en la EI activa.…”
Section: Valoración Del Riesgo Quirúrgicounclassified